THE INFLUENCE OF NGAPAK ACCENT STUDENTS ON SPEAKING ENGLISH IN PURWOKERTO - Ramadhan, Daris; Wijaya, Armeria; Lestari, Sri (Universitas PGRI Sumatera Barat, 2023)
Mispronunciation of English consonants by students often occurs when Purwokerto students speak English. These factors play an important role in understanding English communication. The aims of this research are to 1) analyze affect students' English pronunciation when speaking English and 2) analyze students' perspectives on English with a Ngapak accent. Narrative research is a design of inquiry from the humanities in which the researcher studies the lives of individuals and asks them to provide stories about their lives. Internal and external pronunciation motivation of each respondent. In this research there were 5 respondents who were Purwokerto students studying at Wijaya Kusuma University in Purwokerto. The study was conducted through recording and transcription of respondents. The results of this study found that in each respondent there must be differences in the sound of English, and there are several factors that cause different English pronunciation, namely intrinsic factors and external factors. Intrinsic factors from self-confidence, interest, and motivation, if from extrinsic factors it can be from the environment and support from the closest people. Purwokerto students make numerous mispronunciations in English consonants, with 27 errors made by 5 respondents. The study found that each person's pronunciation factor and motivation differ, and the plugs or medhok used are not the same for everyone. The results suggest that each person's pronunciation factor and motivation are unique, and the study highlights the importance of understanding and addressing these differences in pronunciation to improve students' English pronunciation.